A kid like Jake [videorecording (DVD)] - Parsons, Jim, 1973-; Danes, Claire, 1979-; Chopra Jonas, Priyanka; Spencer, Octavia; Pearle, Daniel (Shout! Factory, 2018)
A Brooklyn couple has always known that their four-year-old son is more interested in fairy tale princesses than toy cars. But when his preschool director points out that his gender-nonconforming play may be more than a phase, the couple is forced to rethink their roles as parents and spouses as they apply for him to go to a private kindergarten in New York City.